Profiling Oman education data using data mining approach - Alalawi, Sultan Juma Sultan; Mohd Shaharanee, Izwan Nizal; Mohd Jamil, Jastini (IP Publishing LLC, 2017)
Nowadays, with a large amount of data generated by many application services in different learning fields has led to the new challenges in education field. Education portal is an important system that leads to a better development of education field. This research paper presents an innovative data mining techniques to understand and summarizes the information of Oman’s education data generated from the Ministry of Education Oman “Educational Portal”. This research embarks into performing student profiling of the Oman student database. This study utilized the k-means clustering technique to determine the students’ profiles. An amount of 42484-student records from Sultanate of Oman has been extracted for this study. The findings of this study show the practicality of clustering technique to investigating student’s profiles.Allowing for a better understanding of student’s behavior and their academic performance. Oman Education Portal contain a large amounts of user activity and interaction data.Analyses of this large data can be meaningful for educator to improve the student performance level and recognize students who needed additional attention.